Adaptacyjne aspekty hominizacji Część II. Przystosowania pokarmowe - Kujawa, Betina (Polskie Towarzystwo Antropologiczne, 1994)
ADAPTATIVE ASPECTS OF HOMINIZATION. PART II. NUTRITIVE ADAPTATIONS. Both some geological, climatic and material traces that are used in paleonthology let reconstruct the complex of the adaptative traits that were developed in Australopithecines. The environmental conditions of South-Eastern Africa in late Pliocene and early Pleistocene directed some morphological, physiological and behavioural changes which the first hominids underwent.
ADAPTATIVE ASPECTS OF HOMINIZATION. PART II. NUTRITIVE ADAPTATIONS